Den partiska omsorgen i elevrelationer - Norgren-Hansson, Mimmi (Utbildning & Lärande, 2023)
This article delves into the dynamics of care within peer relationships, examining how care is expressed between the caregiver and the recipient of care, as well as their broader connections with others. Based on qualitative interviews with twelve pupils, this study investigates the experience of giving and receiving care, particularly in relation to partial friendships. The results uncover two key dimensions of care: internal care, which influences the motivation, understanding, reciprocity and continuity of care within the caregiver-recipient relationship, and external care, which extends beyond this relationship to encompass aspects such as social inclusion and support during conflicts. This research underscores the pivotal role of partiality in shaping the dynamics of care and raises questions about its implications within an educational environment. Furthermore, it contributes to the framework of care ethics, stimulating a philosophical discourse on the moral aspects of partiality in an educational context.